(untitled) - Dunning, John H. (Boston, 1981)
The book provides a comprehensive and detailed review of both the theoretical and policy issues at a time when the subject had reached a watershed, after the controversies of the 1970s; provides a balanced discussion of major themes such as the development of modern theories of international production; the impact of the MNE on the nation-state and the structure of the international market; the response of governments and the appropriate framework for policy measures; and the historical context and likely future of the MNE
Keywords: International business enterprises,Doanh nghiệp kinh doanh quốc tế